(untitled) (The International Journal for Scientific Research, 2024)
In my thesis, I explore the multifaceted challenges and solutions surrounding iron deficiency without anemia (IDWA), a condition often overlooked in clinical settings despite its significant impact on individual well-being and societal costs. I address critical questions related to the symptoms, diagnostic challenges, management issues, long-term implications, and effective treatment strategies for IDWA through a qualitative research methodology. My findings reveal a diverse range of symptoms often misattributed to other conditions, inconsistencies in diagnostic criteria, and a pressing need for tailored management approaches. Long-term studies highlight the socioeconomic burdens associated with untreated IDWA, reinforcing the necessity for improved awareness and personalized treatment plans. By synthesizing patient experiences and expert insights, my research contributes valuable knowledge to the field of hematology and offers practical recommendations for enhancing clinical practice and healthcare policy.